Low-voltage and controllable-developed actuator with bilayer structure based on triple-shape actuation. (3rd May 2022) - Sun, Wen-Jin; Guan, Yan; Jia, Li-Chuan; Li, Yue; Huang, Hua-Dong; Wang, Yue-Yi; Tang, Jian-Hua; Yan, Ding-Xiang; Li, Zhong-Ming
Abstract: Multiple-Shape memory polymers containing conductive particles are seen as potential soft actuators due to their superiority in remote operation and simple equipment. Though abundant conductive particles can reduce the actuating voltage, it has a risk of reducing the shape-memory effect. Bilayer structure is a good strategy to solve the above contradictions. Herein, a low-voltage, controllable-developed, and triple-shape actuator with bilayer structure is prepared successfully. The dense and thin conductive layer brings excellent electrical heating performance to the triple-shape carbon nanotubes (CNTs)/poly(ethyl vinyl acetate) (EVA)/polycaprolactone (PCL) composite without degradation of the actuation. Therefore, low voltages (15–18 V) can heat the CNT/EVA/PCL composite up to 60–100 °C to actuate multiple-shape transition. Various desired patterns upon actuation based on controllable and programming performance can be easily designed based on the resultant composite, such as retrorse and stepwise actuation. Moreover, the actuator could be designed into a "flower" shape to imitate blooming and withering. The low-voltage, controllable-developed and triple-shape actuator based on bilayer structure make it be potential in applications of soft robots and spaceflight fields. Graphical abstract: Image 1